Frontier technologies in infrastructure engineering - International Workshop on Frontier Technologies for Infrastrctures Engineering (2008 : Taipei, Taiwan); Chen, Shi-Shuenn; Ang, Alfredo Hua-Sing, 1930- (Boca Raton : CRC Press, 2009)
06